Evaluation of Patients Presenting to the Emergency Service with Shoulder Dislocation - Abuzer, Abuzer; Eren, Mehmet; Korkmaz, İlhan; Al, Behçet; Zengin, Suat; Eren, Şevki Hakan (European Journal of Therapeutics, 2023)
Objective: Glenohumeral joint dislocation is the most common major joint dislocation in the entire body. This study is an epidemiologic and demographic investigation of dislocated shoulder cases presenting to the emergency room of a public hospital. Methods: This study includes patients that presented to the emergency room of Sivas public hospital with a dislocated shoulder between the dates 01/02/2015-01/01/2018. Patients that were admitted to the emergency room and diagnosed with shoulder dislocation were informed about the study. Results: Five hundred and eighty one patients presenting to Sivas public hospital and diagnosed with shoulder dislocation were included in the study. The average age of patients was 43±18.59, with the youngest patient 19 years old and the oldest 88 years old. 537 (92.4%) patients had anterior, 32 (5.5%) patients had posterior and 12 (2.1%) patients had inferior dislocations. Conclusion: Shoulder dislocation cases are commonly seen in emergency rooms. It is more commonly seen in males and the most frequently seen type is anterior dislocation. This condition concerning individuals of all age groups develops mainly due to trauma.Despite the fact that shoulder dislocations can be diagnosed and treated easily in emergency rooms, prevention of shoulder dislocations can only be achieved by means of preventive measures and informative meetings.